A semiotic analysis and cultural values of Malaysia automotive tv advertisements - Chou En-I; Baharuddin Mohd Arus; Saniah Ahmad (Penerbit UMS, 2017)
Advertising is one of the marketing strategies to promote products to consumers. In fact, semiotic helps to get messages across to audiences in a persuasive way. This paper examines automotive TV advertisements in Malaysia to determine how advertisers seek to achieve their primary goal of persuading or influencing an audience by the use of both language and visual semiotic. How the advertisements encode national identity and cultural values is discussed. Semiotics’ theory can be used as references for the Malaysian car advertising development, such as content analysis, semiology, audience research and in-depth interviews with advertising practitioners, media and opinion leaders are the main components of the data collection. Malaysia, with its ethnic, language and religious differences is an obvious choice of research to observe possible cultural influences on business practices. The ways in which the semiotic interact with each other within an advertisement is discussed, and these are related to the construction of cultural identities. This research is helpful and beneficial to finalize which are the most effective style of advertising in automotive sales, which they can adopt to achieve the best results. The findings suggests some significant implications which helps advertisers to create better local advertisements.